An ontology-driven multimedia focused crawler based on linked open data and deep learning techniques - Capuano, Andrea; Rinaldi, Antonio M.; Russo, Cristiano (Multimedia tools and applications, 2020)
Web-page indexing and classification have been studied extensively starting from the early WWW years. A smart intelligent web agent called focused crawler is a specific software able to seek web pages that are relevant to a particular topic domain. In this article we propose a novel approach to focused crawling based on the use of both textual and multimedia web page content. In our approach we define a novel strategy to choose if a web page should be further explored. We implement our framework in a system which aims to improve the crawling task using semantic based techniques and combining the results with novel technologies like convolutional neural networks and linked open data. Our framework uses ontologies to correlate different topics and understanding their relationships. The correlation among topics is used to improve a textual topic detection step. These results are combined with multimedia analysis and classification based on convolutional neural networks to extract image features. Experimental results are also presented and discussed in order to measure the effectiveness of our framework compared with other approaches using a ground truth composed of web pages about a specific domain.